Minimum wages and vocational training incentives in Germany - Kim Leonie Kellermann (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2017)
This paper examines the impact of sector-specific minimum wages in Germany on the willingness of youths to undergo vocational training. The theoretical impact of wage floors on educational incentives is ambiguous: on the one hand, they raise the opportunity cost of education and prevent further skill accumulation. On the other hand, they lower the employment probability of unskilled workers which promotes additional training. We use a GSOEP-based sample of youths aged 17 to 24, covering a time period between 1994 and 2014 in order to estimate the probability of opting for an apprenticeship employing a mixed logit model. Contrasting with evidence from other countries, we find that increasing sectoral wage floors have a positive effect on already high training probabilities of youths. In case of binding minimum wages, demand for unskilled workers declines which lowers the opportunity cost of education. This effect is reinforced by high requirements concerning professional skills.
Keywords: C33; I21; I28; J24; 330